Histopathological analysis of apoptotic cell count and its role in oral lichen planus - Doddawad, Vidya G (Medknow Publications & Media Pvt Ltd, 2014)
AIM OF THE STUDY: To identify and count the number of apoptotic cells in oral lichen planus (OLP) and correlate with the degree of keratinization, thickness of epithelium and thickness of lymphocytic infiltration of OLP. MATERIALS AND METHODS: The study comprised 40 diagnosed cases of OLP. Sections were stained with hematoxylin and eosin to identify and count the number of apoptotic cells. Measurement of other histopathological parameter of OLP such as degree of keratinization, thickness of epithelium and thickness of lymphocytic infiltration was done by using stage micrometer and eyepiece graticule. Statistical analysis was done to understand the correlation between apoptotic cells and histopathological features of OLP. RESULT: The result showed that the number of apoptotic cells increased, with an increase in thickness of lymphocytic infiltration and degree of keratinization, but there was a decrease in the epithelial thickness. CONCLUSION: Further immunological and molecular studies are required for a stronger evidence in correlating apoptotic cell and histological parameters of OLP.